1919
DOI: 10.1007/bf02872428
|View full text |Cite
|
Sign up to set email alerts
|

Über sprach-, musik- und rechenmechanismen und ihre lokalisationen im großhirn

Abstract: Die wissenschaftliche Periode der Hirnforschung rechnet noch kaum 60 Jahre. Und doch muB ein jeder, der der Entwicklung dieser Forschung gefolgt ist, einr~umen, dab ihre Fortschritte im VerhKltnis zu der verflossenen Zeit enorm sind. Die Oberfl~che des Gehirns ist nicht mehr, wie Flourens, gestiitzt auf unvollst/~ndige Experimente, behauptete, eine gleichfOrmig gebaute und funktionierende Masse, sondern ~vir kOnnen zur Zeit die Richtigkeit der schon 200 Jahre n. Chr. aufgeworfenen Behauptung des Galen s, und s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(29 citation statements)
references
References 0 publications
3
24
0
2
Order By: Relevance
“…Our findings are, therefore, in accordance with results from lesion studies which show that acalculia is more commonly associated with left than right hemisphere damage (Cipolotti, Butterworth, & Denes, 1991;Delazer & Butterworth, 1997;Grafman et al, 1982;Henschen, 1919;Mayer et al, 1999;Sandrini, Miozzo, Cotelli, & Cappa, 2003) and with brain imaging studies showing a left-sided activation in numerical comparison (Pesenti et al, 2000;Fias et al, 2003) or a left-sided predominance (Pinel et al, 1999). During comparisons of various continua, Fulbright, Manson, Skudlarski, Lacadie, and Gore (2003) observed overlapping intraparietal activation for judgments of letter, number, and size ordering, though the left supramarginal gyrus was involved in the distance effect with numbers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are, therefore, in accordance with results from lesion studies which show that acalculia is more commonly associated with left than right hemisphere damage (Cipolotti, Butterworth, & Denes, 1991;Delazer & Butterworth, 1997;Grafman et al, 1982;Henschen, 1919;Mayer et al, 1999;Sandrini, Miozzo, Cotelli, & Cappa, 2003) and with brain imaging studies showing a left-sided activation in numerical comparison (Pesenti et al, 2000;Fias et al, 2003) or a left-sided predominance (Pinel et al, 1999). During comparisons of various continua, Fulbright, Manson, Skudlarski, Lacadie, and Gore (2003) observed overlapping intraparietal activation for judgments of letter, number, and size ordering, though the left supramarginal gyrus was involved in the distance effect with numbers.…”
Section: Discussionsupporting
confidence: 91%
“…It has been indicated that this ability is specifically associated with neural circuitry relaying in the inferior parietal lobule (IPL). Brain damage to these circuits can cause highly specific impairments in the representation and manipulation of numbers (Dehaene & Cohen, 1997;Delazer & Benke, 1997;Grafman, Passafiume, Faglioni, & Boller, 1982;Henschen, 1919;Mayer et al, 1999) while functional imaging techniques have revealed that this region is active during number processing and calculation (Chochon, Cohen, van de Moortele, & Dehaene, 1999;Dehaene, 1996;Naccache & Dehaene, 2001;Pinel et al, 1999, Pinel, Dehaene, Riviere, & Le Bihan, 2001Pesenti, Thioux, Seron, & De Volder, 2000;Piazza, Mechelli, Butterworth, & Price, 2002;Zago et al, 2001). Moyer and Landauer (1967) were the first to describe the existence of quantitative number representations in humans, but many researchers before them (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper focuses on this last issue, taking into account the considerable progress that has recently been made in neuroimaging methods. The involvement of parietal cortex in number processing was initially discovered on the basis of lesion data (Gerstmann, 1940;Hécaen, Angelergues, & Houillier, 1961;Henschen, 1919). Subsequently, a systematic activation of the parietal lobes during calculation, together with precentral and prefrontal cortices, was discovered (Roland & Friberg, 1985) and extensively replicated using positron emission tomography (PET) Pesenti, Thioux, Seron, & De Volder, 2000;Zago, Pesenti, Mellet, Crivello, Mazoyer, & Tzourio-Mazoyer, 2001) and later fMRI (Burbaud, Camus, Guehl, Bioulac, Caille, & Allard, 1999;Rueckert et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1919, the Swedish physician Salomon Henschen [4] observed that patients with specific brain lesions could no longer work with numbers. He termed this disturbance "acalculia" (Greek a-for "not" and Latin calculare for "to calculate").…”
Section: Neuronal Representation Of Absolute Magnitudementioning
confidence: 99%